2010
DOI: 10.1089/ars.2009.3065
|View full text |Cite
|
Sign up to set email alerts
|

Oxidant Production, oxLDL Uptake, and CD36 Levels in Human Monocyte–Derived Macrophages Are Downregulated by the Macrophage-Generated Antioxidant 7,8-Dihydroneopterin

Abstract: The severity of atheroma burden in patients strongly correlates to increasing levels of plasma neopterin, the oxidation product of 7,8-dihydroneopterin. Interferon-γ stimulation of macrophages causes the synthesis of 7,8-dihydroneopterin, a potent antioxidant that inhibits oxidative damage to cells, and the cytotoxicity of oxidized low-density lipoprotein (oxLDL) to monocyte-like U937 cells but not THP-1 cells. With human monocyte-derived macrophages (HMDMs), oxLDL triggered a large oxidative stress, causing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 53 publications
0
10
0
2
Order By: Relevance
“…Necrotic core progression is likely due to the formation of cholesterol crystals in the cytosols leading to inflammasome activation and subsequent IL-1α/β production [32]. In addition M1 macrophages can contribute to oxidative stress observed in the plaque via the production of hydrogen peroxide, superoxides, neopterin (the oxidized product of 7, 8-dihydroneopterin) and myeloperoxidases [33, 34]. These radicals can promote further oxidation of LDLs within the plaques, as well as the initiate of endoplasmic reticulum stress that can initiate apoptosis.…”
Section: B the Arterial Microenvironment In Atherosclerosismentioning
confidence: 99%
“…Necrotic core progression is likely due to the formation of cholesterol crystals in the cytosols leading to inflammasome activation and subsequent IL-1α/β production [32]. In addition M1 macrophages can contribute to oxidative stress observed in the plaque via the production of hydrogen peroxide, superoxides, neopterin (the oxidized product of 7, 8-dihydroneopterin) and myeloperoxidases [33, 34]. These radicals can promote further oxidation of LDLs within the plaques, as well as the initiate of endoplasmic reticulum stress that can initiate apoptosis.…”
Section: B the Arterial Microenvironment In Atherosclerosismentioning
confidence: 99%
“…We have previously shown that 2 μmol/L of 7,8-dihydroneopterin inhibits LDL oxidation [13], although 50-100 μmol/L is required to prevent oxLDL-or HOCl-induced cell death [16][17][18]. It is possible that macrophage cell death occurs at a very localised cellular level, so concentrations of 7,8-dihydroneopterin around the cells may reach protective levels.…”
Section: Discussionmentioning
confidence: 99%
“…Neopterin causes significant cellular stress at elevated concentrations [10][11][12], while 7,8-dihydroneopterin has been shown to be a potent antioxidant capable of inhibiting copper, peroxyl radical and cell-mediated oxidisation of low-density lipoprotein (LDL) [13][14][15]. Macrophage uptake of oxidised LDL (oxLDL) is decreased by 7,8-dihydroneopterin-mediated down-regulation of the CD36 scavenger receptor [16]. Macrophage necrosis by HOCl, oxLDL and peroxyl radicals is also inhibited by 7,8-dihydroneopterin [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To manage this re-equilibrium of oxidation, pro-oxidant mechanisms can be reduced and/or antioxidant mechanisms can be increased, with the latter being the most applied approach. In relation to its effect on oxLDL, antioxidants have been shown to decrease oxLDL levels after administration of the antioxidant cumin 175 and the macrophage-generated antioxidant 7,8-dihydroneopterin, 176 proving antioxidants as a proper approach to decrease oxLDL.…”
Section: Antioxidantsmentioning
confidence: 99%